The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/gps.4381
|View full text |Cite
|
Sign up to set email alerts
|

Reducing suicidal ideation in home health care: results from the CAREPATH depression care management trial

Abstract: Objectives The study evaluated the effectiveness of a depression care management intervention in reducing suicidal ideation (SI) among home health patients. Methods Data come from the cluster-randomized effectiveness trial of the Depression Care for Patients at Home (Depression CAREPATH), an intervention that integrates depression care management into the routine nursing visits of Medicare home health patients screening positive for depression. Patients were interviewed at baseline, 3, 6, and 12 months follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…There were limited comparison studies in this population, using the same scale. However, this result is higher than the 4.9% of suicidal ideation found in community residents in Taiwan [12], the 10% of Medicare home health patients in the USA [26], but similar to a report of 12.4% for individuals with physical disabilities in Germany [27]. The finding also echoed a result from South Korea, in which Lee, et al [10] reported that the hazard ratio of suicide people with disability was 1.9-fold higher, compared to individuals without disability.…”
Section: Resultsmentioning
confidence: 55%
“…There were limited comparison studies in this population, using the same scale. However, this result is higher than the 4.9% of suicidal ideation found in community residents in Taiwan [12], the 10% of Medicare home health patients in the USA [26], but similar to a report of 12.4% for individuals with physical disabilities in Germany [27]. The finding also echoed a result from South Korea, in which Lee, et al [10] reported that the hazard ratio of suicide people with disability was 1.9-fold higher, compared to individuals without disability.…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, some studies have highlighted a higher risk of suicidal behaviour in women[ 39 , 52 ] and White Caucasian[ 25 ]. In the same vein, Lohman et al [ 47 ] observed lower scores in the HDRS among older adults from ethnic minority groups. On the other hand, the study by Bartels et al [ 41 ] reported higher scores of suicidal ideation among older Americans from Asian ethnic groups (in comparison to those from the African ethnic group).…”
Section: Resultsmentioning
confidence: 92%
“…Several studies showed an increased risk for suicidal behaviour with higher disability levels[ 20 , 22 , 40 , 42 , 47 , 48 ], poorer health status[ 22 , 39 ], and multimorbidity[ 41 , 47 ]. Almeida et al [ 2 ] studied the relationship of multiple clinical factors with suicide attempt and completed suicide among older men from Australia.…”
Section: Resultsmentioning
confidence: 99%
“…These settings offer opportunities for detecting those at risk and implementing prevention strategies. Indeed, a depression management intervention resulted in a reduction in suicidal ideation for Medicare home health patients (Lohman et al, 2016). In addition, recent VHA clinical innovations have focused on the importance of suicide prevention among HBPC and recently discharged CLC populations (Luci et al, 2020;Mlinac et al, 2021).…”
Section: Introductionmentioning
confidence: 99%